Feasibility study of an electrodialysis system for in-home water desalination in urban India - Kishor G. Nayar; Prithiviraj Sundararaman; Catherine L. O'Connor; Jeffrey D. Schacherl; Michael L. Heath; Mario Orozco Gabriel; Sahil R. Shah; Natasha C. Wright; Amos G. Winter (Development Engineering, 2017)
Poor quality of drinking water delivered to homes by state utilities, and a large reliance on brackish ground water resources in parts of urban India, has resulted in the adoption of in-home water treatment solutions. The only existing in-home water treatment solution capable of desalination is reverse osmosis (RO). However, existing RO products can recover only 25-50% of the feed water supplied as usable product water. In this study, an alternative solution that relies on electrodialysis (ED) was designed and experimentally shown to achieve a recovery of 80%, producing 12L/h of water at the desired salinity of 350ppm from a feed salinity of 3000ppm. The cost and size of the proposed system were also found to be comparable to existing in-home RO systems. In-home ED water treatment systems could compete with existing RO products while providing the advantage of improved water-conservation in water-stressed India.
Keywords: 330; Brackish water; Desalination; Electrodialysis; Reverse osmosis